CONDITION AND DEVELOPMENT OF UNPLANNED TOURISM BUSINESS IN TASIKMALAYA DISTRICT - Muhammad Indra Gunawan -; Tutut Sunarminto; Adjat Sudrajat (Media Konservasi, 2022)
Tourism activities in Tasikmalaya Regency were recorded to experience fluctuations in the number of tourist visits from year to year. There are two classifications of tourist objects in Tasikmayala Regency, namely legal and registered tourist objects and tourist objects that are not legal and not yet registered in the Disparpora Tasikmalaya Regency and the Disparbud of West Java Province. Tourism objects that are not yet legal, have not been recorded, grow from the initiative of tourists or the community, and are not yet well established in their management are referred to as unplanned tourism businesses. The study was conducted to describe the conditions and developments in the unplanned tourism business carried out in three locations, namely Pasir Kirisik, Bukit Panyangrayan, and Bukit Puji Ningrum by conducting direct observations, interviews, and questionnaires. All data collected were then analyzed descriptively covering the general condition of the research location, characteristics of tourists and local communities, perceptions, motivations, preferences, participation, and conditions of business development factors in each research location. The condition of the unplanned tourism business shows that it is running well even though it has not run optimally and is accepted by tourists and the local community. So it is important the role of stakeholders according to their capacity and capability as part of the support system for procedural acceleration of an unplanned tourism business into an established ecotourism business. Key words: acceleration, ecotourism, established, intuitive, tourism business